Entropy-based classification of trust factors for cloud computing. (14th September 2020) - Sharma, Ankita; Munjal, Puja; Banati, Hema
Cloud computing has now been introduced in organisations all around the globe. With the developing prevalence of grid and distributed computing, it has become incredibly important to maintain security and trust. Researchers have now begun concentrating on mining information in cloud computing and have begun distinguishing the basic factor of moral trust. Moral angles in the cloud rely upon the application and the present conditions. Data mining is a procedure for distinguishing the most significant data from a lot of irregular information. In this paper, a three phased methodology is adopted, involving machine learning techniques to discover the most important parameter on which trust is based in the cloud environment. The methodology was then implemented on data sets, proving privacy is the most important factor to calculate ethical trust in cloud computing. The results can be employed in real cloud environments to establish trust as service providers can now consider privacy as the main issue in this relatively new distributed computing environment.